Pharmacokinetic Comparisons of Different Combinations of Yigan Jiangzhi Formula in Rats: Simultaneous Determination of Fourteen Components by UPLC-MS/MS - Yang Wang; Ping Wang; Jun Xie; Zhaorui Yin; Xiaoyan Lin; Yuanhong Zhao; Zheng Li; Tao Chen; Shuang Gu; Qiang Lv; Zhili Zhao; Changhua Xu (Journal of Analytical Methods in Chemistry)
A rapid, specific, and sensitive analysis for simultaneous determination of fourteen components (daidzein, fermononetin, apigenin, luteolin, puerarin, ononin, calycosin-7-O-β-D-glucoside, tanshinol, rosmarinic acid, alkanoic acid, salvianolic acid B, berberine, jatrorrhizin, and palmatine) of Yigan Jiangzhi formula (YGJZF, a clinical experienced formula for damp-heat syndrome) in rat plasma was developed and validated using ultraperformance liquid chromatography coupled with mass spectrometry. Lower limit of quantitation ranged from 0.2–10.0 ng/mL, and the calibration curves showed good linearity over 500 times of measuring range. The validated method was successfully applied to the pharmacokinetics investigation of the fourteen compounds in rat plasma after oral administration of two different doses of YGJZF. Compared with the low-dose group of YGJZF, the high-dose group showed significant increase (P<0.01 or P<0.05) in maximum plasma concentration, maximum concentration time, and area under the plasma concentration-time curve and decrease (P<0.01 or P<0.05) in clearance of most of the fourteen analytes, which suggested that the bioavailability of these components could be enhanced by increasing dosage. The above results may provide useful information for cognizing the relationship between in vitro and in vivo data of the fourteen bioactive ingredients of YGJZF and further guiding rational clinical drug prescription.